2009
DOI: 10.1590/s1516-35982009000300016
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de lisina digestível para frangos de corte machos no período de 37 a 49 dias de idade

Abstract: Digestible lysine levels for male broilers in the period from 37 to 49 days of age ABSTRACT -One thousand and fifteen commercial male broilers from 37 to 49 days of age were used to evaluate different digestible lysine levels. A completely randomized trial was used, with five treatments (0.90, 0.95, 1.00, 1.05 and 1.10% of digestible lysine, respectively), seven repetitions and 35 experimental units, with 29 birds each. Lysine levels were added in isoenergetic (3,250 kcal of ME/kg) and isoproteic (18% of CP) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
1
2
0
4
Order By: Relevance
“…The protein deposition in the carcass increased linearly (P<0.06 and P<0.02), respectively, as the lysine levels in the diet were increased, regardless of how (diets CSM and CSM + IAA) (Figure 3). This response pattern confirms the reports of Temim et al (2000), Kidd et al (2004), Corzo et al (2004), Trindade Neto et al (2009 and Ghahri et al (2010), that the lysine requirement for maximum deposition of protein in the carcass is higher than that for maximum weight gain.…”
Section: Resultssupporting
confidence: 91%
“…The protein deposition in the carcass increased linearly (P<0.06 and P<0.02), respectively, as the lysine levels in the diet were increased, regardless of how (diets CSM and CSM + IAA) (Figure 3). This response pattern confirms the reports of Temim et al (2000), Kidd et al (2004), Corzo et al (2004), Trindade Neto et al (2009 and Ghahri et al (2010), that the lysine requirement for maximum deposition of protein in the carcass is higher than that for maximum weight gain.…”
Section: Resultssupporting
confidence: 91%
“…Os níveis de lisina digestível não afetaram as porcentagens de extrato etéreo e proteína bruta nas vísceras e no sangue. A ausência de variação significativa confirma que a lisina não é direcionada para o sangue e as vísceras (Trindade Neto et al, 2009). A concentração de zinco, no entanto, foi determinante na composição média do extrato etéreo e da proteína dessa fração (vísceras e sangue).…”
Section: Resultsunclassified
“…One factor that can influence fat deposition is the balance of amino acids, since excess protein or its low digestibility can lead to an increase in FDR. Thus, the objective was to meet the requirements in amino acids, seeking maximum protein deposition and lower fat deposition (Trindade Neto et al, 2009). Bolu et al (2012) found no difference in the protein retention rate in broilers fed up to 100 g/kg dry distillers' grains to replace corn in diets.…”
Section: Resultsmentioning
confidence: 99%